Fraction of spectral solar radiance transmitted through snow and sea ice as measured in different depths under sea ice (transflectance) at station PS122/4_46-174 on 2020-07-10, survey 2, version 2.0 - Philipp Anhaus; Stefanie Arndt; Christian Katlein; Daniela Krampe; Benjamin Allen Lange; Ilkka Matero; Julia Regnery; Jan Rohde; Martin Schiller; Marcel Nicolaus (PANGAEA, 2025)
Transmitted solar radiance was measured using an ARC (Advanced-Radiance-Collector) RAMSES hyper-spectral radiometer (TriOS) mounted on the ROV during the MOSAiC expedition between November 2019 and September 2020 and normalized by the incident solar irradiance as measured using an ACC (Advanced-Cosine-Collector) RAMSES hyper-spectral radiometer (TriOS) installed on the sea ice. All times are given in Universal Coordinated Time (UTC).
In: Anhaus, P et al. (2025): Spectral solar radiation over and under sea ice during the MOSAiC expedition 2019/20, version 2.0 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.979856